Preliminary Study of In-Action Learning: An Analysis of Mathematical Connection Abilities of Junior High School Students - R, Nurmala; Alfian Mucti; Achmad Zultan Mansur; Eka Widyawati; Jusmawati (International Journal of Technology and Education Research, 2026)
This article examines mathematical connection ability, an essential competency emphasized in the National Council of Teachers of Mathematics (NCTM) recommended mathematics learning objectives. Specifically, this research aims to describe students' mastery of mathematical connection ability in the topic of Quadrilaterals and Triangles. Employing a descriptive qualitative methodology, the research instrument consisted of three essay-type test questions on mathematical connection ability, which were implemented to collect data. Data analysis revealed that the average percentage of students' achievement in mathematical connection ability was 30%. These findings indicate that middle school students' mastery of the mathematical connection ability in the topics of quadrilaterals and triangles remains relatively low. The results of this study provide educators with a foundation for designing more effective learning experiences to enhance students' mathematical connection ability. The importance of developing this ability lies not only in fostering a deep conceptual understanding but also in applying mathematics in broader contexts, both within and outside the field of mathematics.